Graphical User Authentication Algorithms Based on Recognition: A survey - Saadi , Zena M.; Sadiq , Ahmed T.; Akif , Omar Z. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
In cyber security, the most crucial subject in information security is user authentication. Robust text-based password methods may offer a certain level of protection. Strong passwords are hard to remember, though, so people who use them frequently write them on paper or store them in file for computer .Numerous of computer systems, networks, and Internet-based environments have experimented with using graphical authentication techniques for user authentication in recent years. The two main characteristics of all graphical passwords are their security and usability. Regretfully, none of these methods could adequately address both of these factors concurrently. The ISO usability standards and associated characteristics for graphical user authentication and possible attacks on nineteen recognition-based authentication systems were discussed. In this study, differentiation table of attack patterns for all recognition-based techniques is shown. Finally, the positive and negative aspects of nineteen methods were explained in the form of a detailed table.